2019
DOI: 10.1620/tjem.249.231
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Thyroid Peroxidase Antibody Is Associated with Lower Placental Weight in Maternal Thyroid Dysfunction

Abstract: Thyroid dysfunction (TD) is caused by thyroid peroxidase (TPO) antibody, as seen in Hashimoto's disease. TD is a common problem of reproductive age and may impair fetal development. Here, we determined the effect of TPO antibody on perinatal outcomes in Japanese women with TD before conception. A retrospective study involving cases of maternal TD with term singleton birth was conducted. The subjects with TD were divided into two groups according to the presence (n = 22) or absence (n = 20) of TPO antibody. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…maternal, infant, and placental weight gain. However, TPO-Ab may also have played a role, as recent studies have shown that placental and fetal birth weights were lower in TPO-Ab-positive subjects (18)(19)(20). Therefore, we adjusted for fT4 and TPO-Ab separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…maternal, infant, and placental weight gain. However, TPO-Ab may also have played a role, as recent studies have shown that placental and fetal birth weights were lower in TPO-Ab-positive subjects (18)(19)(20). Therefore, we adjusted for fT4 and TPO-Ab separately.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, we thought that the changes in metabolic status caused by thyroid cancer treatment and TSH suppressive therapy altered the body’s metabolic status and reduced maternal, infant, and placental weight gain. However, TPO-Ab may also have played a role, as recent studies have shown that placental and fetal birth weights were lower in TPO-Ab-positive subjects ( 18 – 20 ). Therefore, we adjusted for fT4 and TPO-Ab separately.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy women with positive TPO‐Ab had a higher prevalence of anxiety and depression than that of pregnant women without TPO‐Ab 32 . Besides, pregnant women with TPO‐Ab+ were reported to have lower placental and birthweight, and a higher incidence of gestational diabetes mellitus 33 …”
Section: Discussionmentioning
confidence: 99%
“…32 Besides, pregnant women with TPO-Ab+ were reported to have lower placental and birthweight, and a higher incidence of gestational diabetes mellitus. 33 As the incidence of TPO-Ab increases with advanced age, 15 it is speculated that the increased risk of pregnancy loss in women with TPO-Ab may be due to the confounding effect of aging. In this study, there were no significant differences in age distributions between the four study groups, and TPO-Ab + and TPO-Ab − women (30.68 ± 4.5 vs 31.34 ± 4.90, P = .323).…”
Section: Roc Curve Analysis For Tpo Predicting Pregnancy Outcomementioning
confidence: 99%
“…Both hypothyroidism/SCH [ 12 , 24 , 25 ] and TPO Ab-positivity [ 14 , 19 , 26 ] were suggested to be associated with a higher risk of GDM, and this risk is further increased when these statuses co-occur [ 24 , 27 ]. However, this pattern could not be supported in several other studies, as no significant associations between these factors were identified [ 14 , 17 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%